PC index as a ground-based indicator of the solar wind energy incoming into the magnetosphere: (1) relation of PC index to the solar wind electric field EKL - Troshichev, O. A. (Frontiers in Astronomy and Space Sciences, 2022)
. The polar cap magnetic activity PC index was approved by IAGA as a proxy for energy that enters into the magnetosphere during solar wind-magnetosphere coupling (IAGA Resolutions, 2013, 2021). The paper summarizes experimental results attesting the validity of this PC index essence. The following issues are examined: the PC index derivation method, making allowance for regular and irregular variations of ionospheric conductivity; relationships between the PC index and solar wind electric field (EKL) and factors controlling response of PC index to the EKL field alterations; relation of PC index to the magnetospheric field-aligned currents (FAC) and to solar wind dynamic pressure pulses (Pdyn). The PC index alterations in course of 23/24 solar activity cycles have been analyzed in relation to various solar wind parameters and the conclusion was made that linear link between the PC index and solar wind electric field EKL remained valid irrespective of solar activity cycle. New ideas concerning (1) the nature of occasional differences between the PC indices in summer and winter polar caps and (2) two simultaneously acting mechanisms of the solar wind influence on the magnetosphere (Dungey and Tverskoy concepts) are discussed, as a result of the PC index application. It is emphasized that the ground-based PC index ensures a permanent on-line information on geoefficiency of the solar wind impact on the magnetosphere and, correspondingly, on the varying geophysical situation.